2016
DOI: 10.1088/1757-899x/117/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Misorientations in spheroidal graphite: some new insights about spheroidal graphite growth in cast irons

Abstract: Abstract. Local diffraction patterning, orientation mapping and high resolution transmission electron microscopy imaging have been used to characterize misorientations in graphite spheroids of cast irons. Emphasis is put here on bulk graphite, away from the nucleus as well as from the outer surface of the spheroids in order to get information on their growth during solidification. The results show that spheroidal graphite consists in conical sectors made of elementary blocks piled up on each other. These block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…This was long ago postulated for spheroidal graphite by Mitsche et al 26 and demonstrated with transmission electron microscopy (TEM) by Miao et al 27 The schematic of compacted graphite proposed by Den Xijun et al 28 and the scanning electron microscopy (SEM) observations by Geier et al 29 may be similarly understood. TEM observations of chunky graphite showed the same thing 30 which appears well in line with the schematic proposed by Loper et al 31 for this degenerate graphite. From the above observations, it may be concluded that graphite growth in cast irons always proceeds along the prismatic direction, whatever is the apparent growth direction that the overall shape suggests.…”
Section: Graphite Growthsupporting
confidence: 88%
“…This was long ago postulated for spheroidal graphite by Mitsche et al 26 and demonstrated with transmission electron microscopy (TEM) by Miao et al 27 The schematic of compacted graphite proposed by Den Xijun et al 28 and the scanning electron microscopy (SEM) observations by Geier et al 29 may be similarly understood. TEM observations of chunky graphite showed the same thing 30 which appears well in line with the schematic proposed by Loper et al 31 for this degenerate graphite. From the above observations, it may be concluded that graphite growth in cast irons always proceeds along the prismatic direction, whatever is the apparent growth direction that the overall shape suggests.…”
Section: Graphite Growthsupporting
confidence: 88%
“…In all tested specimens, the traces of the radial crack initiation were observed not only in central disgregations, but also at the G-M interface (Figures 6 and 15-18), what was previously mentioned in the work of Cooper et al [8]. The misorientation of graphene blocks between sectors [25,34], especially in large spheroids, could be not enough to accommodate all network mismatches that resulted from the multiplication of grown ledges [25,34]. Therefore, internal areas of open volume defects, and even small cavities on the matrix-graphite interface (Figures 9 and 10), seem to be preferred initiation sites of radial cracks.…”
Section: Discussion Of the Resultssupporting
confidence: 74%
“…The binding energy of Van der Waals bonds (7 kJ/mol) connecting the basic graphene planes in the elementary cell along the "c" direction, is rather small as compared to the binding energy of covalent bonds (524 kJ/mol) between carbon atoms in the graphene plane along the "a" direction ( Figure 1a) [11,23]. The covalent bonds in the basic plane (along the "a" direction) were less often broken also due to their more random orientation relative to the direction of tensile stress [34,35]. Thus, both types of internal cracks identified in the observed graphite spheroids usually passed through the area of weakened cohesion, the radial cracks along sector boundaries, and the peripheral cracks between individual graphene plates.…”
Section: Discussion Of the Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…2-a), giving features that would agree with the observation of sectors. However, transmission electron microscopy (TEM) observations have shown that the orientation of the c axis along a sector tilts at random and in either ways [10] which implies that continuous growth around a screw dislocation did not occur. The second type of models ( Fig.…”
Section: Introductionmentioning
confidence: 99%